Answer:
(4y + 7)(y + 2)
So y = -7/4 and -2
Step-by-step explanation:
Given the below quadratic expression;
![4y^2+8y+7y+14](https://img.qammunity.org/2023/formulas/mathematics/college/sf3jy9ohq176bmus3whyqd4qp26r0i3as7.png)
Let's go ahead and group the factors as shown below;
![4y(y+2)+7(y+2)](https://img.qammunity.org/2023/formulas/mathematics/college/18ujtmgh8dxcve331ossfq6bt3k3l5stbd.png)
This will give us;
![(4y+7)(y+2)](https://img.qammunity.org/2023/formulas/mathematics/college/k7lxjg6ccp8463khaz23gyzrol5b6aw4ix.png)
So if we equate (4y + 7) to zero, we'll have;
4y + 7 = 0
4y = -7
y = -7/4
Also,
y + 2 = 0
y = -2